2018
DOI: 10.3329/bjar.v43i4.39157
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and profitability of improved versus existing cropping pattern in Kushtia region

Abstract: The trial was conducted at Multi Location Testing (MLT) site under On-Farm Research Division, BARI, Kushtia during the last week of February, 2015 to second week of February, 2017 at farmers’ field condition to cover two cropping cycle of four crops. The main objectives of the trial were to verify the feasibility of growing improved cropping pattern Mustard-Mungbean-T.Aus-T.Aman rice and to compare its productivity and profitability with existing cropping pattern Lentil-Sesame-T.Aman rice. The varieties BARI S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Cropping system intensification from double (rice-rice or rice-wheat) to triple cropping system (Wheat-Mungbean-T. Aman) increased the system REY by 10-75% in the High Ganges River Floodplain and Madhupur tract of Bangladesh [5,32,33]; three times more in the active Brahmaputra-Jamuna Floodplain Chars of Bangladesh [34], but 42% more wheat equivalent yield (WEY) in India [35], as well 82% higher system REY when compared to double to four crop-based systems [36]. In other, reported that cropping system intensification from three to four crop-based system increased system REY by 38-44% across the different agroecological zones of Bangladesh [37][38][39], similar to our study, whereas it was lower by 26% [40] and much higher (81%) as reported by Islam et al [41] compared to our study. In the recent, Saha et al [42] reported cropping system intensification increased 211 to 360% more REY by two to four crop based cropping system in the salt-affected coastal zones of Bangladesh.…”
Section: Crop and System Rice Equivalent Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Cropping system intensification from double (rice-rice or rice-wheat) to triple cropping system (Wheat-Mungbean-T. Aman) increased the system REY by 10-75% in the High Ganges River Floodplain and Madhupur tract of Bangladesh [5,32,33]; three times more in the active Brahmaputra-Jamuna Floodplain Chars of Bangladesh [34], but 42% more wheat equivalent yield (WEY) in India [35], as well 82% higher system REY when compared to double to four crop-based systems [36]. In other, reported that cropping system intensification from three to four crop-based system increased system REY by 38-44% across the different agroecological zones of Bangladesh [37][38][39], similar to our study, whereas it was lower by 26% [40] and much higher (81%) as reported by Islam et al [41] compared to our study. In the recent, Saha et al [42] reported cropping system intensification increased 211 to 360% more REY by two to four crop based cropping system in the salt-affected coastal zones of Bangladesh.…”
Section: Crop and System Rice Equivalent Yieldmentioning
confidence: 99%
“…The gross margin of the improved (T. Aman-potato-cucumber-T. Aus) cropping systems was US$ 1426-1805 ha −1 , much higher (74%) compared to the existing (T. Aman-potato-T. Boro) cropping system, with an average net return of US$ 1617 ha −1 . The intensification and diversification from three to four crop based cropping system increased gross margin by 13-29% [38,40]; even though doubled from in Mustard-Mungbean-T. Aus-T. Aman (1914 US$ ha −1 ) cropping system compared to Mustard-Dibbled Aus-T. Aman (924 US$ ha −1 ) cropping system [41]. In another, Alam et al [5] reported that intensification from double to triple cropping system increased gross margin by 26% and net return by double due to higher returns and lower production cost in the High Ganges River Floodplain of Bangladesh.…”
Section: Crop and System Profitabilitymentioning
confidence: 99%
“…Grain/tuber yield of Potato, Boro, Radish, and T. Aman were 26.40, 5.46, 20.29, and 4.19 t/ha, it's between, in the second cycle of alternative cropping pattern, while in the current pattern grain/tuber yield of Potato, Boro, and T. Aman were 26.81, 5.59, and 5.10 t/ha, in both. Rahman et al [7] realized similar results.…”
Section: Grain/tuber Yieldmentioning
confidence: 62%
“…Simultaneously, cropping severity and output can be amplified [4], [6]. Furthermore, several reports on cropping patterns indicate that an added crop could be familiarized with minimal variations or substituted for current crops to significantly increase farmers' productivity and profitability [7]- [13]. Cropping intensity must be increased to crop more food on a limited volume of property, and thus more suitable crop(s) should be included in the cropping pattern.…”
Section: Introductionmentioning
confidence: 99%